Asynchronous-Synchronous Teaching Techniques to Reinforce Achievement in Grade 2 Mathematics - Arnel S. Travero; Nancy T. Rubin (Basic and Applied Education Research Journal, 2021)
This study aimed to explore teaching techniques that would reinforce academic achievement in Mathematics of Grade 2 pupils in Camp Evangelista Elementary School in Cagayan de Oro City, Philippines for school year 2020-2021. Asynchronous and Synchronous teaching techniques were employed in the class. The instruments used in the study were the School Learning Modules (SLMs) crafted and provided by the Department of Education, the video lessons patterned from the SLMs, the First and Second Quarter grades that represent their achievements in Mathematics, and the Reflection papers submitted by the pupils every grading period for feedbacking. The study was quantitative in nature and data gathered were analyzed using frequency, percentage, and paired sample t-test. Findings revealed that there was a significant difference in the academic achievement of the pupils in Mathematics after exposure to Synchronous and Asynchronous learning as evident in the Second Grading grades. It was disclosed that the intervention employed to reinforce pupils’ achievement in Mathematics is effective in this new normal learning. The researchers recommend that teachers may use this teaching technique to reinforce achievement particularly in Mathematics.